2020
DOI: 10.1155/2020/1473981
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Diagnostic Delay in Amyotrophic Lateral Sclerosis: The Role of Nonneurologist Practitioners

Abstract: Introduction. Amyotrophic lateral sclerosis (ALS), usually fatal in a few years, is a neurodegenerative disorder where the diagnostic delay, although variable according to the studies, remains too long. The main objective of this study was to determine the average time to diagnose ALS and the role of each physician, general practitioner (GP), or specialist (neurologist or not) involved in the management of these patients. The secondary objective was to propose some simple schemes to quickly identify an ALS sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This has been confirmed in other research as well (11)(12)(13)(14), including more recent studies in 2020 that found a median delay of about 12 months (15-17) and a mean delay of 17 months (15). In the Richards et al article, the longest delay was 27 months, reported in a study reviewing the United States Centers for Medicare & Medicaid Services database (18) and shortest reported median interval was from a study of a national database used by tertiary ALS clinics in France, reporting a delay of 9.1 months (19).…”
Section: Length Of Diagnostic Delay In Alssupporting
confidence: 82%
See 4 more Smart Citations
“…This has been confirmed in other research as well (11)(12)(13)(14), including more recent studies in 2020 that found a median delay of about 12 months (15-17) and a mean delay of 17 months (15). In the Richards et al article, the longest delay was 27 months, reported in a study reviewing the United States Centers for Medicare & Medicaid Services database (18) and shortest reported median interval was from a study of a national database used by tertiary ALS clinics in France, reporting a delay of 9.1 months (19).…”
Section: Length Of Diagnostic Delay In Alssupporting
confidence: 82%
“…Clinical presentation plays a significant role in time to diagnosis, particularly with regards to bulbar versus spinal-onset presentation (8,13,15,16,18,19,21,22,(25)(26)(27)(28)(29)(30)(31), with the literature suggesting patients with bulbar-onset ALS experience a delay to diagnosis three to seven months shorter than those with spinal-onset ALS (21,(26)(27)(28). The study reporting the longest delay of 2.25 years, as mentioned in the review paper by Richards et al (10), showed a substantial difference between delays in the bulbar-onset group (1.25 years) compared to the spine-onset group (2.5 years) (18).…”
Section: Disease Phenotype and Diagnostic Delaymentioning
confidence: 99%
See 3 more Smart Citations